Methanol Production via CO2 Hydrogenation: Sensitivity Analysis and Simulation—Based Optimization - Borisut, Prapatsorn; Nuchitprasittichai, Aroonsri (Frontiers in Energy Research, 2019)
Carbon dioxide (CO2) is one of greenhouse gases, which can cause global warming. One of studies to mitigate CO2 emissions to the atmosphere is to convert CO2 to valuable products (i.e. methanol). To make methanol production via CO2 hydrogenation a competitive process, the optimal operating conditions with minimum production cost need to be considered. This paper studied an application of response surface methodology in optimization of methanol production via CO2 hydrogenation. The objective of this optimization was to minimize the methanol production cost per tons produced methanol. The sensitivity analysis was performed to determine the parameters that show significant impacts on the methanol production cost. Response surface methodology coupled with nonlinear programming solver were used as the optimization tool. The results showed response surface methodology was successfully applied to the methanol production via CO2 hydrogenation process. The obtained minimum methanol production cost was $565.54 per ton produced methanol with the optimal operating conditions as follows. Inlet pressure to the first reactor: 57.8 bar, Inlet temperature to the first reactor: 183.6 ◦C, Inlet pressure to the second reactor: 102.6 bar, Outlet temperature of the liquid stream cooler after the second reactor: 63.5 ◦C, Inlet temperature to the first distillation column: 51.8 ◦C.